Features of radiological and physiological findings in pulmonary capillary hemangiomatosis: an updated pooled analysis of confirmed diagnostic cases. (December 2019) - Anazawa, Rie; Terada, Jiro; Sakao, Seiichiro; Shigeta, Ayako; Tanabe, Nobuhiro; Tatsumi, Koichiro
Pulmonary capillary hemangiomatosis (PCH) is a very rare and refractory disease characterized by capillary angioproliferation. The updated classification of pulmonary hypertension categorizes PCH into a subgroup of pulmonary arterial hypertension (PAH) alongside pulmonary veno-occlusive disease (PVOD). However, the definitive diagnosis of PCH only with noninvasive tools remains difficult. The aim of this study was to elucidate the radiological and physiological characteristics of PCH. We searched for cases of pathologically confirmed PCH in the English literature published between 2000 and 2018. We identified 26 cases among 39 studies. Then, we extracted and evaluated the relevant clinical information in all cases with available data. On chest computed tomography (CT), ground-glass opacities (GGOs) were observed in 92% of the cases, in which poorly defined nodular pattern was the most common (88%). GGOs in a bat-wing distribution were observed in one case. Septal lines and lymph node enlargement were observed less frequently (each 19%, 12%). Seven cases (27%) had overlapping abnormalities. Diffusing capacity of the lung for carbon monoxide (DLCO ) was remarkably decreased. Alveolar hemorrhage by histological findings or bronchoalveolar lavage (BAL) was observed in seven cases. The present study showed that the most characteristic findings of CT in PCH was centrilobular GGOs with a poorly defined nodular pattern, and septal lines and lymph node enlargement were seen less frequently. Alveolar hemorrhage detected by BAL and decreased DLCO may also be helpful to recognize the possibility of PCH like PVOD.